Rabbit Acceptability of Defatted Coconut Flour Among Different Food Sources - Acosta Acosta, Yanixi; La O Michel, Ángel Luis; Valdivié Navarro, Manuel; Betancourt Santos, Nelson Nixon; Villalón Moracen, Yudelkis (Universidad Pedagógica y Tecnológica de Colombia, 2021)
To determine the acceptability of defatted coconut flour supplied as the sole feed and incorporated at different levels in the rabbit diet, two experiments were performed in which random block designs were used. In the first experiment the treatments were: T1 corn flour, T2 alfalfa flour, and T3 defatted coconut flour. In the second, the treatments consisted of supplying the diets with the inclusion of defatted coconut flour in growing percentage (0, 10, 20, 30 and 40 %). In both studies Chinchilla breed male rabbits of 80 days old were used, weighting an average of 2,150 ± 103 g, 21 and 35 rabbits respectively. Variables attempt to consume and food consume showed similar results, both in defatted coconut flour supplied as the sole feed and when mixed with other ingredients. Animals made consumption attempts for nearly 24 hours and the highest consumption attempts were observed at night. Animals showed the highest acceptance for diets of 10% defatted coconut flour inclusion. The results suggest defatted coconut flour is an agro-industrial by-product with potentiality to be included in rabbit diets and to substitute traditional feed used for this specie.